COVID-19: Analisis in-Silico Struktur Tersier Nsp1 dan Nsp2 pada SARS-CoV-2 - Suprianto Suprianto; I Made Budiarsa (Politeknik Kesehatan Kemenkes Mamuju, 2020)
The spread of the COVID-19 pandemic has captured a lot of attention from the global community. This pandemic was caused by SARS-CoV-2 by producing nonstructural proteins (nsp1-16). This study aims to analyze the tertiary structure of nsp1 and nsp2 in SARS-CoV-2 in-silico. The target proteins nsp1 and nsp2 have access codes YP_009725297.1 and YP_009725298.1 obtained from NCBI. The amino acid composition of nsp1 and nsp2 is 19774.35 Daltons and 70507.81 Daltons, respectively. The nsp1 tertiary structure produces a model structure with a percentage of 64%, 19% disordered area, 42% alpha-helix, 13% beta strand, 92.17% model verification (passed), 74.0% favored region and 6.4% outliers area (stable). The nsp2 tertiary structure produced a model structure with a percentage of 9%, 17% disordered area, 36% alpha-helix, 27% beta strand, 64.29% model verification (failed), 76.0% favored region and 16.4% outliers area (unstable). The stability of nsp1 has very good potential compared to nsp2, the validation of the structure obtained can be the basis for studying the development of the vaccine design for the SARS-CoV-2 virus that causes COVID-19.